2003
DOI: 10.1063/1.1578527
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous carbon films prepared by the “dip” technique: Deposition and film characterization

Abstract: Several nondestructive characterization techniques (optical and photothermal deflection spectroscopy in the visible photon energy range, Raman spectroscopy, profilometry, photoluminescence, electron-spin-resonance characterization of the paramagnetic centers, etc.) are used to study the properties of the a-C:H:OH films deposited by the “dip” technique. With such a preparation method, the substrates are dipped in viscous mixtures of liquid carbon compounds. The subsequent baking in an oven at different temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…Amorphous carbons, including our sputtered films, usually display broad asymmetric C(1s) lines; , the presence of a highly symmetric line therefore suggests that the sample undergoes graphitization during annealing. This is often observed after thermal treatment of amorphous carbons, which tends to increase the sp 2 /sp 3 carbon ratio. The rapid annealing under H 2 /N 2 atmosphere has also the effect of reducing the oxygen content in the carbon film, as evidenced by the fact that the A O(1s) / A C(1s) ratio decreases from a typical value >0.09 to 0.04.…”
Section: Resultsmentioning
confidence: 99%
“…Amorphous carbons, including our sputtered films, usually display broad asymmetric C(1s) lines; , the presence of a highly symmetric line therefore suggests that the sample undergoes graphitization during annealing. This is often observed after thermal treatment of amorphous carbons, which tends to increase the sp 2 /sp 3 carbon ratio. The rapid annealing under H 2 /N 2 atmosphere has also the effect of reducing the oxygen content in the carbon film, as evidenced by the fact that the A O(1s) / A C(1s) ratio decreases from a typical value >0.09 to 0.04.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements, including the Raman and Fourier transform infra-red (FTIR) spectra [7], of the sp 2 and sp 3 (and/or sp 2 /sp 3 ratio) contents present in the films were often used to determine the carbon phases. In a previous report a range of a-C:H films were deposited at various baking temperatures and were studied by thickness (≈0.3-1.2 µm), Raman spectroscopy, FTIR, electron spin resonance and other methods [8]; the results showed that the carbon phase changed with the temperature during deposition. X-ray absorption near-edge structure (XANES) spectra are convenient and useful for accurately determining the sp 2 and sp 3 contents in the film's surface, because graphite and diamond phases yield very different spectra.…”
Section: Introductionmentioning
confidence: 98%
“…The glossy metallic appearance of this black coating on shells heated above 500°C can possibly be explained by structural modification of the layer due to release of O and H, previously reported to occur between 450°C and 500°C (Ray et al . ). Heating in an oxidizing atmosphere produced larger colour variation.…”
Section: Resultsmentioning
confidence: 97%